The emerging paradigm of calcium homeostasis as a new therapeutic target for protozoan parasites. Issue 1 (13th April 2021) - Gupta, Yash; Goicoechea, Steven; Pearce, Catherine M.; Mathur, Raman; Romero, Jesus G.; Kwofie, Samuel K.; Weyenberg, Matthew C.; Daravath, Bharathi; Sharma, Neha; Poonam; Akala, Hoseah M.; Kanzok, Stefan M.; et al.
Abstract: Calcium channels (CCs), a group of ubiquitously expressed membrane proteins, are involved in many pathophysiological processes of protozoan parasites. Our understanding of CCs in cell signaling, organelle function, cellular homeostasis, and cell cycle control has led to improved insights into their structure and functions. In this article, we discuss CCs characteristics of five major protozoan parasites Plasmodium, Leishmania, Toxoplasma, Trypanosoma, and Cryptosporidium . We provide a comprehensive review of current antiparasitic drugs and the potential of using CCs as new therapeutic targets. Interestingly, previous studies have demonstrated that human CC modulators can kill or sensitize parasites to antiparasitic drugs. Still, none of the parasite CCs, pumps, or transporters has been validated as drug targets. Information for this review draws from extensive data mining of genome sequences, chemical library screenings, and drug design studies. Parasitic resistance to currently approved therapeutics is a serious and emerging threat to both disease control and management efforts. In this article, we suggest that the disruption of calcium homeostasis may be an effective approach to develop new anti‐parasite drug candidates and reduce parasite resistance. Highlights: This article maps out known small molecule agents interfering with calcium as well as critical target gene sets which have been scantily explored. Calcium homeostasis is critical for agility, metamorphosis, intracellular survival, and host cell invasion and egress essential for Apicomplexan and Kinetoplexan parasite pathogenesis. The article explored calcium channels as a treasure trove for target based drug discovery, since ion channels are the most drugable class of proteins and these genes bear relatively low homology with the human host.